Effect of Fuzheng Huayu capsule combined with Pegasys on genotype 1 hepatitis C fibrosis and cell apoptosis - ZHANG, BO (D.A. Spandidos, 2014)
The aim of the present study was to observe the effects of Fuzheng Huayu capsule combined with Pegasys (peginterferon α-2a) on hepatic fibrosis in rats and in the treatment of patients with genotype 1 hepatitis C and hepatic cirrhosis. A dimethylnitrosamine (DMN)-induced rat model of liver injury was established. Fuzheng Huayu capsule combined with Pegasys was administered to the rats and the DMN-induced hepatocyte apoptosis was observed. In addition, a total of 100 patients with genotype 1 hepatitis C and hepatic cirrhosis were treated by oral administration of Fuzheng Huayu capsule combined with Pegasys or with Pegasys alone. The therapeutic effect of Fuzheng Huayu capsule combined with Pegasys was analyzed. Following the oral administration of Fuzheng Huayu capsule combined with Pegasys to the DMN model rats, the expression of α-smooth muscle actin was found to be significantly reduced, hemopoietic stem cell apoptosis was increased and liver cell apoptosis was reduced. These indices were significantly different compared with those in the model group (P<0.05). Liver function and liver fibrosis were markedly recovered in hepatitis C patients with hepatic cirrhosis following treatment with the combination treatment compared with those in the patients treated with Pegasys alone (P<0.05). In conclusion, the combination of Fuzheng Huayu capsule with Pegasys inhibited liver fibrosis and cell apoptosis, and may be a novel therapeutic strategy for the treatment of patients with compensated cirrhosis due to hepatitis C. This study provides a method for the optimization of existing treatment strategies and for the establishment of potentially effective combination therapies.